MULTI-RESPONSE OPTIMISATION OF MACHINING PARAMETERS IN TURNING AISI 304L USING DIFFERENT OIL-BASED CUTTING FLUIDS (Nigerian Journal of Technology, 2019)
Properties of melon seed and beniseed oils which are considered as “environmentally” friendly oils were investigated and the performance evaluation of the formulated beniseed and melon seed oil- based cutting fluids were carried out. American Iron and Steel Institute (AISI) 304L alloy steel was used as workpiece and tungsten carbide as cutting tool, while commercial mineral oil- based cutting fluid was used as a control experiment. The viscosities of the melon seed oil and beniseed oil- based cutting fluids were 1.53 mm2/s and 0.86mm2/s, while their pH values were 8.2 and 8.7 respectively. The optimal multi-response turning parameters was achieved using cutting speed of 159 rev/min (level 3), feed rate of 0.9 mm/rev (level 3), depth of cut of 1 mm (level 2) and type of cutting fluid of 1.53mm/s (level 3). The ANOVA results show that feed rate has the most significant effect on the surface roughness (92.93%) and cutting temperature (27.51%). http://dx.doi.org/10.4314/njt.v38i2.13